Pengaruh Kualitas Pelayanan dan Citra Merek terhadap Kepuasan Penumpang Maskapai Wings Air di Bandar Udara Sultan Muhammad Kaharuddin Sumbawa - Hilda Fatricia Noviantika; Djoko Widagdo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Wings Air is a low-cost airline in Indonesia and is a subsidiary of the company PT. Lion Grub. The purpose of this research is to determine the influence of service quality and brand image variables on passenger satisfaction with Wings Air at Sultan Muhammad Kaharuddin Airport, Sumbawa, both partially and simultaneously. The method used is a quantitative method with non-probability sampling and purposive sampling techniques distributed through a questionnaire of 100 respondents. This research instrument uses a Likert scale with 22 statements according to the indicators of each variable. This research uses SPSS for descriptive analysis and testing classical assumptions and hypothesis testing, namely multiple linear regression analysis tests. The service quality variable gets a t-count > t-table result of 2,809 > 1.984 with a significance value of 0.006 < 0.05 and the brand image variable gets a t-count > t-table value of 2,313 > 1,984 with a significance value of 0.023 < 0.05. The results of this research indicate that the variables of service quality and brand image have a partial effect on passenger satisfaction. The variables of service quality and brand image simultaneously influence passenger satisfaction with an f-count > f-table value of 10,975 > 3.09 and a significance of 0.000 < 0.05 with an influence size of 16.8%.